Gravity Reduced Nitrogen Uptake via the Regulation of Brace Unilateral Root Growth in Maize Intercropping - Chen, Guopeng; Liang, Bing; Bawa, George; Chen, Hong; Shi, Kai; Hu, Yun; Chen, Ping; Fan, Yuanfang; Pu, Tian; Sun, Xin; Yong, Taiwen; Liu, Weiguo; et al. (Frontiers in Plant Science, 2021)
Water, nutrient, light, and interspecific facilitation regulation of soil physicochemical properties and root morphology modulate the nitrogen (N) uptake in cereal and legume intercropping systems. However, the maize root morphological plasticity and the N uptake capability response to gravity in intercropping system remains to be determined. Maize was grown under 20 cm (I20), 40 cm (I40), and 60 cm (I60) of narrow row spacing in an intercropping system (maize-soybean strip relay-intercropping) and equal row spacing of monoculture (M) in a 2-year field experiment. As supplementary for the field experiment, maize root barrier and plant inclination experiments were conducted. Plant inclination, brace root morphological, N uptake, indole-3-acetic acid (IAA) level, IAA synthesis genes, grain yield were assessed. The result showed that the plant inclination increased with decreasing narrow row spacing in intercropping. These phenomena still exist at the root barrier experiment. Moreover, the brace unilateral root growth ratio (BURR) increases with increasing plant inclination in intercropping treatments. The plant inclination experiment showed nearly all the brace unilateral root growth after inclination at 45° with a rope to pull. BURR tended to be a significant positive correlation (P=0.00) with plant inclination. Thus, gravity (plant inclination) causes brace unilateral root growth. Otherwise, IAA concentration of stem nodes (which developed into brace root) in wide row increase as plant inclination increases. The Zmvt2 and ZM2G 141383 genes (associated with IAA biosynthesis) were highly expressed in a wide row. There was a strong correlation (P=0.03) between the IAA concentration of wide row and BURR. Therefore, gravity regulates the IAA level, which affects brace root unilateral growth. Additionally, the brace root number, volume, and surface area were decreased when BURR increased. Subsequently, the leaf N, cob N, and kernel N accumulation were reduced. These organs N and grain yield in I60 were not significantly different compared to M.The excessive brace unilateral root growth is not conducive to N uptake and increase yield. Our results suggest that gravity is an essential factor in regulating root morphology plasticity by IAA level, decreasing N uptake capacity. Furthermore, these results indicate plant inclination can regulate root phenotype and N uptake.